Predictor-corrector procedures for pseudo-dynamic tests - Bonelli, Alessio; Bursi, Oreste S. (Engineering computations, 2005)
Purpose - To propose novel predictor-corrector time-integration algorithms for pseudo-dynamic testing.Design methodology approach - The novel predictor-corrector time-integration algorithms are based on both the implicit and the explicit version of the generalized-α method. In the non-linear unforced case second-order accuracy, stability in energy, energy decay in the high-frequency range as well as asymptotic annihilation are distinctive properties of the generalized-α scheme; while in the non-linear forced case they are the limited error near the resonance in terms of frequency location and intensity of the resonant peak. The implicit generalized-α algorithm has been implemented in a predictor-one corrector form giving rise to the implicit IPC-ρ∞ method, able to avoid iterative corrections which are expensive from an experimental standpoint and load oscillations of numerical origin. Moreover, the scheme embodies a secant stiffness formula able to approximate closely the actual stiffness of a structure. Also an explicit algorithm has been implemented, the EPC-ρb method, endowed with user-controlled dissipation properties. The resulting schemes have been tested experimentally both on a two- and on a six-degrees-of-freedom system, exploiting substructuring techniques.Findings - The analytical findings and the tests have indicated that the proposed numerical strategies enhance the performance of the pseudo-dynamic test (PDT) method even in an environment characterized by considerable experimental errors. Moreover, the schemes have been tested numerically on strongly non-linear multiple-degrees-of-freedom systems reproduced with the Bouc-Wen hysteretic model, showing that the proposed algorithms reap the benefits of the parent generalized-α methods.Research limitations implications - Further developments envisaged for this study are the application of the IPC-ρ∞ method and of EPC-ρb scheme to partitioned procedures for high-speed pseudo-dynamic testing with substructuring.Practical implications - The implicit IPC-ρ∞ and the explicit EPC-ρb methods allow a user to have defined dissipation which reduces the effects of experimental error in the PDT without needing onerous iterations.Originality value - The paper proposes novel time-integration algorithms for pseudo-dynamic testing. Thanks to a predictor-corrector form of the generalized-α method, the proposed schemes maintain a high computational efficiency and accuracy.